Magnetotransport studies of antidot superlattices in coupled two-dimensional electron-hole gases - Stadelmann, T; Kardynal, B; Nicholas, R; Takashima, K; Mason, N (2002)
Magnetotransport measurements have been performed in strongly coupled two-dimensional electron-hole gases in an InAs Gash heterostructure in the presence of antidot potentials of different strengths. We have observed commensurability features in the magnetoresistance that we attribute to high mobility electrons. It is proposed that they can be observed due to magnetic breakdown, despite the fact that the electron-hole mixing is found to play an important role. (C) 2002 Elsevier Science B.V. All rights reserved.